Methodological Proposal for the Assessment of Company Sustainability in Transport Logistics - Fernandes, Alexandre Chacon; Tagliaferro, Evandro Roberto; Vanzela, Luiz Sergio (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2022)
The sustainability of companies is a principle that is increasingly defining their development and growth, with the valuation of the market and products and services, having the principles of the United Nations Global Compact as the guidelines for achieving sustainability. In the case of a logistics for a transportation company, it is necessary to carry out a diagnosis of performance to then establish an action plan that aims at its sustainability, called SustainablePlan for Transport Logistics (SPTL). Therefore, the objective of this work was to develop a methodology for the diagnosis, allowing the company to classify its sustainability and guide it in the elaboration of the action plan in the short, medium and long term of the SPTL. The principle was to develop an objective method to classify the level of sustainability of a company based on a final score, determined by means of parameters modified from the principles of theUN Global Compact, called "principles of sustainability". The method was then applied to a transportation company located in the Northeast of São Paulo. We conclude that the proposed method allowed us to classify the company's sustainability as moderate, as well as to identify the points that need action to achieve full sustainability, acting with respect to the principles of human rights and labor, environment and anti-corruption.